Ambient electric arc ionization for versatile sample analysis using mass spectrometry. Issue 18 (16th August 2021) - Gao, Yuanji; Li, Yuan; Zhan, Binpeng; He, Quan; Zhu, Heping; Chen, Weiwei; Yin, Qi; Feng, Hongru; Pan, Yuanjiang
Abstract : Ambient electric arc ionization mass spectrometry (AEAI-MS) was developed for the analysis of various organic compounds having a wide range of polarities, ranging from non-polar to highly polar species. Abstract : A novel, convenient ambient electric arc ionization (AEAI) device was developed as a mass spectrometry ion source for versatile sample analysis. AEAI could be considered as a soft ionization technique in which the protonated ion ([M + H] + ) is the main ion species with little or no in-source fragmentation for most analytes. Coupled with a high-resolution Orbitrap mass spectrometer, AEAI could be applied to the analysis of a variety of organic compounds having a wide range of polarities, ranging from non-polar species such as polybenzenoid aromatic hydrocarbons (PAHs) to highly polar species such as amino acids. With its versatile capabilities in the mass spectrometric analysis of small molecules, AEAI has the potential to be an alternative to traditional ionization methods such as electrospray ionization (ESI), atmospheric pressure chemical ionization (APCI), and electron impact (EI) ionization. The limitations of AEAI are also discussed.